إدارة الموارد البشرية ودورها في فعالية فرق العمل دراسة حالة بمؤسسة سونلغاز - أوذاينية لينة; البوطي مروة; ريان آمنة (جامعة عمار ثليجي الاغواط, 2022)
The study aimed to recognize the role of human resources management in its dimensions (recruitment, training, motivation, career path, performance evaluation) on the effectiveness of the work teams at The Sonelgaz Foundation in Laghouat We adopted the questionnaire as a study tool, which included a set of phrases that included the axes of the study, and we, as researchers, relied on the descriptive analytical approach, and we questionned a sample of (50) individuals, where (36) questionnaires were retrieved which was valid for the study. The statistical program smart pls was used to test the hypotheses of the study using the following statistical tools (arithmetic mean, standard deviation...) Through this, a set of results was obtained, the most important of it is that there is an efficacy of human resource management in the work teams among individuals working in Sonelgaz Corporation - Laghouat - embodied in the employment dimension.